Seismic Performance Evaluation of Irregular Auditorium Building based on ASCE 41-23 - Fiqhunissa, Ananda Elnish; Iman Satyarno; Angga Fajar Setiawan; Mariyana Aida Ab Kadir; Darmawan, Muhamad Fauzi (Journal of the Civil Engineering Forum, 2024)
This study discusses the seismic performance evaluation of an irregular auditorium building. The building is an educational facility which has roof span up to 46 meters, column height up to 10 meters, beam span up to 15 meters, cantilever up to 6.50 meters, 2 inclined columns with the angle up to 54.72°, and 1 transfer column with 1 transfer beam. The evaluation process was carried out using Tier 3 method with linear dynamic procedure which consisted of Response Spectrum Analysis (RSA) and Linear Time History Analysis (LTHA) according to ASCE 41-23 using SAP2000 subjected to short (S s ) and long (S ) period of earthquakes. The building is designed to Risk Category IV, which the target performance levels for structural components are Immediate Occupancy (IO) for Basic Safety Earthquake 1 for New Building (BSE-1N) and Life Safety (LS) for Basic Safety Earthquake 2 for New Building (BSE-2N). Even though the building had a torsional strength irregularity, the percentage of components with a Demand-Capacity Ratio value that did not meet the requirements was 9.87% of the total components; hence the linear procedure was assumed to be still applicable. Analyses showed that the average acceptance criteria ratio of the components with the RSA method was lower than with the LTHA method but the percentage of the components with acceptance criteria ratio exceeding 1 using RSA method was higher than using the LTHA method. In addition, the results indicated that the average performance level of the components was IO for BSE-1N and LS for BSE-2N, which both results had met the expected performance level targets. However, the maximum performance level of the components did not meet the IO performance level target for BSE-1N and did not meet the LS performance level target for BSE-2N.